GOLPH3 Promotes Cancer Growth by Interacting With STIP1 and Regulating Telomerase Activity in Pancreatic Ductal Adenocarcinoma - Wang, Kebing; Jiang, Shuai; Huang, Anpei; Gao, Ying; Peng, Baogang; Li, Zhi; Ma, Wenbin; Songyang, Zhou; Zhang, Shihong; He, Meifang; Li, Wen (Frontiers in Oncology, 2020)
Overexpression of Golgi phosphoprotein 3 (GOLPH3) predicts poor prognosis and is a potential therapeutic target in pancreatic ductal adenocarcinoma (PDAC). However, its role and underlying molecular mechanisms in the progression of PDAC remain unknown. In the present study, using high-throughput bimolecular fluorescence complementation (BiFC) analysis, we identified that stress-inducible protein-1 (STIP1) interacts with GOLPH3 and confirmed the interaction using co-localization and co-immunoprecipitation. The levels of GOLPH3 and STIP1 in PDAC tissues and adjacent non-cancerous pancreatic tissues were determined using immunohistochemistry (IHC) and quantitative real-time reverse transcription PCR. Real-time Quantitative-telomere repeat amplification (Q-TRAP) was applied to detect relative telomerase activity, and cell proliferation was measured when small interfering RNAs targeting GOLPH3 or STIP1 were transfected into PDAC cell lines. BALB/c nude mice were used to assess tumor growth inhibition of BXPC3 cells stably transfected with GOLPH3 short hairpin RNA. In summary, GOLPH3 was found to interact with STIP1 and both proteins were overexpressed and co-localized in PDAC tissues and cell lines. Moreover, suppression of GOLPH3 expression using shRNAs in PANC1 and BXPC3 cells inhibited tumor cell proliferation both in vitro and in vivo. Mechanistically, GOLPH3 interacts with STIP1 to activate telomerase reverse transcriptase (hTERT) and telomerase activity by c-Myc, and then upregulates cell cycle-related signaling proteins, including cyclin D1, to promote tumor cell growth, suggesting that disrupting the interaction between STIP1 and GOLPH3 would be a promising new strategy to treat PDAC.